PERENCANAAN ARSITEKTUR SISTEM INFORMASI BERBASIS CLOUD COMPUTING DENGAN MENGGUNAKAN METODE EAP (ENTERPRISE ARCHITECTURE PLANNING) (Studi Kasus: PT. Ma’soem) - Muhamad Fahmi Nugraha (Jurnal Accounting Information System (AIMS), 2020)
PT. Ma'soem is one of Pertamina fuel distributor in West Java, which has 33 retail outlets. The operations are run Pertamina fuel is sold directly to customers and supplying the fuel directly from the manufacturer Pertamina. PT. Ma'soem so far in implementing the business processes have not been using an information system that requires the Enterprise Architecture Planning for PT. Ma'soem. Enterprise architecture models used in this research is by using a model of Enterprise Architecture Planning (EAP). EAP is a process of defining the enterprise architecture, which focuses on data architecture, application and technology in support of business and plans to implement the architecture, where the EAP method, there are several stages ranging assessment of the Initialization of planning (Planning Initiation), Modeling Business (Business Modeling) Systems and Technology today (current Systems & Technology), Architecture Data (Data Architecture), Application Architecture (Applications Architecture), Architectural Technology (Technology Architecture), Plan of Implementation (Implementation Plans).The results of this analysis, information systems on PT. Ma'soem form a blueprint for enterprise architecture planning planing the cloud-based managed defines four core business processes, the data architecture resulted in 17 entities, 6 as well as the application for the technology architecture technology architecture resulted in the proposal.